A Preliminary Randomized Controlled Evaluation of a Universal Healthy Relationships Promotion Program for Youth. (March 2020) - Exner-Cortens, Deinera; Wolfe, David; Crooks, Claire V.; Chiodo, Debbie
Bullying and mental health problems are pressing concerns for adolescents. Given their burden, we need to find efficacious ways to prevent these experiences. However, existing prevention programs tend to be single-issue and may not focus on the universal capacities required to reduce these problems among youth. To this end, we evaluated the universal, small groups Healthy Relationships Plus (HRP) program, which focuses on the promotion of positive mental health and the reduction of bullying and substance misuse. A sample of 212 youth from Southwestern Ontario were randomly assigned to the HRP or an attention-control condition over an 8-day period during summer 2014. Primary outcome measures (i.e., most important outcomes for this evaluation) were positive mental health, bullying victimization/perpetration, and substance misuse (alcohol, marijuana). We also examined a mediator (help-seeking) and two moderators (sex, adverse childhood experiences) of main effects. Participation in HRP was associated with reduced odds of physical bullying victimization at 1-year follow-up, compared with adolescents in the attention-control condition. This finding was mediated by increased intention to seek help from a mental health professional following HRP participation. We did not find main effects for positive mental health or substance misuse in this sample; however, there was an interaction effect whereby youth with significant trauma experiences reported less marijuana use at 1-year follow-up compared with control students. Findings reiterate the importance of help-seeking for bullying prevention and demonstrate the preliminary efficacy of the HRP as a universal strategy for preventing bullying victimization among mid-adolescents within school and community settings.